When the unknown lives next door: a study of central Amazonian anurofauna - Motta, Jessica; Menin, Marcelo; Almeida, Alexandre P.; Hrbek, Tomas; Farias, Izeni Pires (Zootaxa, 2018)
The number of species of anurans in the Amazon is highly underestimated with new studies reporting the discovery of a large number of species every year. This advance in the discovery of biodiversity is due to the use of molecular tools, especially 16S rRNA gene barcoding, which is used to identify species and discover cryptic lineages. Few anurans of the central Amazon have molecular sequence data available in public databases, which contrasts with the considerable species richness of this biome. The aim of the present study was to test for the presence of cryptic species using the mPTP delimitation algorism. We morphologically identified 26 species, of which 23 were confirmed molecularly with the remaining three species identified as other congeneric species, since sequences with the same epithet do not exist in GenBank. Of these 23 species, nine contained one lineage restricted to central Amazon. This represents an underestimate of 39% in the taxonomic diversity in our sample. This is particularly surprising given that our sampling sites are among the best-studied regions of the central Amazon.